IMPLEMENTASI KURIKULUM PEMBELAJARAN MENDALAM BERBASIS STEAM DI TK KANIGARAN PROBOLINGGO - Dwi Ayu Wulandari; May Dwi Ayu Irawati; Murtin; Fitri Silaturahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the implementation of a STEAM-based deep learning curriculum at TK Kanigaran Probolinggo based on the reflective experience of PIAUD students participating in the Field Teaching Practice (PPL) at the Ahmad Dahlan Institute.Deep learning is an approach that emphasizes children's active engagement in exploration, investigation, critical thinking, and problem-solving. The STEAM approach serves as an integrative framework connecting Science, Technology, Engineering, Arts, and Mathematics, thereby allowing for comprehensive and meaningful learning.This study uses a literature review and reflective analysis approach without direct field data, utilizing theories, PAUD (Early Childhood Education) learning guidelines, and the general PPL experiences of students as the basis for analysis. The results of the study indicate that the integration of deep learning and STEAM has significant potential to enhance children's creativity, curiosity, critical thinking skills, and engagement. However, its implementation faces challenges, including limited teacher competency, inadequate facilities and infrastructure, activity planning issues, and time management difficulties.The role of PPL students is crucial as collaborative partners who bring new perspectives and can strengthen the application of innovative learning in PAUD institutions. This research suggests the need for improving teacher competency, developing project-based activities, providing an environment that supports exploration, and optimizing collaboration between teachers and PPL students.